A Fixation-Shadowing Technique for Electron Microscopic Visualization of Platelets, Subcellular Material, and Fibrin - Stewart, G. J (Thrombosis and Haemostasis, 1970)
Plasma components were visualized in three-dimensional detail by a method which depends on attaching plasma components, including platelets and fibrin, to a siliconized surface where they can be fixed, dehydrated and shadowed. Citrated PRP and blood contained a mixed population of discoid and dendritic platelets. Discoid platelets were thin with gently changing elevations and depressions on their surfaces. Dendritic platelets exhibited a random number and arrangement of dendritis. The “bodies” of dendritic platelets appeared to be thicker than discoid platelets. After thrombin action, the “bodies” from which dendrites radiated resembled various irregularly shaped geometric forms whose thickness was approximately equal to their width. Continued thrombin action caused disintegration of platelet membranes.Fibrinogen could not be resolved. However, after thrombin action, extensive polymerization of fibrin monomers into protofibrils about 130 Å wide was observed well before appreciable lateral or vertical polymerization had occurred. Later, large strands with frequent points of Y-type branching were common.The method has clinical potential since the entire procedure is simple and can be completed in less than an hour.